Acute Hepatic Coma Successfully Treated by Extracorporeal Baboon Liver Perfusions. Issue 5791 (1st January 1972) - Abouna, G. M.; Fisher, L. McA.; Still, W. J.; Hume, D. M.
Abstract : Two patients in deep hepatic coma due to fulminant viral hepatitis were treated by extracorporeal baboon liver perfusion after failing to respond to medical treatment and three consecutive exchange transfusions. Both patients recovered full consciousness after one liver perfusion, made a complete recovery, and were leading normal lives seven and eight months after treatment. Perfusions were maintained for 13½ and 16½ hours without complication, and neither clinical immunological reactions nor antibaboon serum antibodies developed as a result of treatment. Whereas normal consciousness could be restored only by liver perfusion, both exchange transfusion and liver perfusion were effective in clearing bilirubin and in raising the level of clotting factors. Extracorporeal baboon liver perfusion provides a safe and effective method for the treatment of acute hepatic coma.